Plan de manejo del lechón y la madre en las granjas porcina de la provincia de el oro - Rojas Ramos, Hector Omar (Machala : Universidad Técnica de Machala, 2022)
Pig farming in our country is one of the most important productive activities in which hundreds of families work due to the great demand of the market in the province of El Oro and Ecuador itself. In this research we highlight each of the processes in which both the piglet and its mother are treated, from the moment of insemination, care in the farrowing pen, feeding the sow, supplements, and the entire process. management that is needed to avoid increasing mortality levels within the herd. The management plan of the piglet and the mother in the pig farms of the Province of El Oro, is an investigation that provides the technical information obtained first-hand in those who are dedicated to this commercial activity. Through this investigative process, an important precedent is set for those who are dedicated to this activity, hoping to be a source of consultation for both experts and those who are new to this production.
La porcicultura en nuestro país es una de las actividades productivas más importantes en las que cientos de familias trabajan debido a la gran demanda que tiene el mercado de la provincia de El Oro y el Ecuador en sí. En la presente investigación destacamos cada uno de los procesos en los cuales tanto el lechón como su madre pasan a ser tratados, desde el momento de la inseminación, los cuidados en la paridera, la alimentación de la cerda, los suplementos, y todo el proceso de manejo que se necesita para evitar que se aumenten los niveles de mortalidad dentro de la piara. El plan de manejo del lechón y la madre en las granjas porcinas de la Provincia de El Oro, es una investigación que proporciona la información técnica obtenida de primera mano en las de aquellos que se dedican a esta actividad comercial.
Keywords: PORCINOS; PRODUCCIÓN; MANEJO; BIOSEGURIDAD